An??lise dos ??rg??os ofertados ?? Central Nacional de Transplantes (CNT) provenientes de doadores idosos - Heinzen, Evelyn (2015)
Organ transplantation is one of the greatest twentieth century advances in medicine, with success rates above 80%. Recent changes on donors profile, due to worldwide population aging, has led to modified organs acceptance criteria by the transplantation centers. This study aimed to describe the epidemiological, serological and clinical data of elderly organ donors, aged 60 years old or above, distributed by the National Transplant Center - NTC, Brazil, from 2011 to 2014, with special regard to organ donations progression and donation processes outcome related to the elderly organs donors. A descriptive, exploratory, retrospective, temporal and documentary series study was conducted with secondary data concerning Brazilian Federal Unit origin (UF), donation processes data and solid organs (heart, lung, liver and kidney) distribution, conducted by NTC, from 2011 to 2014, of older donors with 60 years or above. A total of 1,173 donation processes were analyzed, 38.6% of elderly donors were 60-64 years range and 31.5% were 65-69 years range. 57.9% were men and stroke (haemorrhagic) was the leading cause of death. Santa Catarina (20.2%), Cear?? (13%) and Rio de Janeiro (11.3%) were the most tendered states for national elderly organs distribution. Kidney was the most offered organ, followed by liver, heart and lung, in that order. Potential donor hospital stay was identified as an average of 5 - 6 days. Considering the use of vasoactive drugs and antibiotics, there was not a significant difference between donors with transplanted organs and donors with discarded organs. As for serologic tests, the presence or absence of a positive serologic test did not influence the acceptance of organs; however creatinine, urea and total bilirubin levels influenced this acceptance. Our results suggests that further researches are needed to better understand the old organ donor profile, consequently stimulating the use of organs from these donors by the transplantation centers and state transplant centers.